ANALISIS YURIDIS PENGGUNAAN MATA UANG VIRTUAL (BITCOIN) SEBAGAI SARANA TINDAK PIDANA PENCUCIAN UANG (MONEY LAUNDERING) - Parwoto, Adi; Deliana, Evi; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Rapid technological developments bring progress in almost all aspects of humanlife. In line with the development in this era of globalization, developed also economicactivities that occur in society. One means of payment that developed recently is virtualmoney. Virtual money then started to become a phenomenon in society since theemergence of crypto currency (Cryptocurrency) as a manifestation of technologicaldevelopments in e-commerce activities .. In Indonesia Bitcoin has also been growingvery rapidly, according to one of the exchanger (provider of exchange services, purchase, sending and receiving of Bitcoin) in Indonesia, namely PT.Bitcoin Indonesia through itsWeb page (indodax.com), during the period early 2015 to mid 2018,unfortunately, Along with the development of the virtual currency Bitcoin inIndonesia, there is no regulation governing the use and protection of the law against theBitcoin in Indonesia in eksplisitTidak any special arrangements to Bitcoin is certainly animpact on the users of Bitcoin itself, since Bitcoin itself is very vulnerable Cracking ofthe offenses, hacking and various cybercrime (cybercrime). EvenExecutive Director ofthe Communications Department of Bank Indonesia, Agusman as reported in a writtenstatement print media Tempo, Saturday, January 13, 2018 to give a statement that"Bitcoin prone to be used as a means of money laundering and financing of terrorism(Syberterorism), so it can affect the stability of the financial system and harm thepublic.In Indonesia Money Laundering set in Act No. 8 of 2010 on the Prevention andCombating of Money Laundering Act, but the Act Such Not Set in eksplisif to the use ofvirtual currency (Bitcoin) as a means of laundering money. Though filled fromTheemergence of cases using virtual currency (Bitcoin) as ingredients abroad makes thiscrime as a new threat that must be anticipated as early as possible. As well as theNumber of Users And Values Bitcoin transactions are increasing every year in Indonesia.In this case, need to be analyzed further forms of prevention and penindakanya.Keywords: Virtual Currency – Bitcoin - Crime - Money Laundering